Development and characterization of nuclear microsatellite markers for Eremanthus erythropappus and their transferability across related species - Rocha, Lucas Fernandes [UNESP]; Paula, Natália Ribeiro; Nazareno, Alison Gonçalves; De Carvalho, Dulcinéia (Springer Nature, 2020)
Background: We developed simple sequence repeats (SSR) for Eremanthus erythropappus (DC.) MacLeish, an endangered tree species endemic to the Brazilian Savanna and Atlantic Forest biomes, and tested their transferability to two closely related Eremanthus species. Results: Using a genomic library enriched with tandem repeat motifs, we identified 16 primer pairs, and characterized them in two populations. Nine primers amplified the expected size fragments and seven SSRs were polymorphic, providing a total of 38 alleles and an average of 4.22 alleles per marker. The polymorphic information content (PIC) ranged from 0.44 to 0.94 with an average of 0.65. The average observed heterozygosity across all loci varied from 0.61 to 1.00. The observed (H O ) and expected (H E ) heterozygosity within the two populations varied from 0.65 to 1.00 and from 0.31 to 1.00, respectively. Conclusions: These newly developed SSR markers are a powerful tool for population genetic analyses and may be useful in studies on species ecology, evolution, and taxonomy.
Keywords: Eremanthus erythropappus; Eremanthus glomerulatus; Eremanthus incanus; Genetic diversity; Simple sequence repeats